Analytical Studies on Attitude of Teachers Trainees for Inclusion of Sex Education: Exploring Attitudes towards Sex Education among Teachers Trainees (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Respect for the rights of each and every child to life, safety, growth, and educationalopportunity permeates every facet of the school and the larger educational community. Studying howB.Ed. students and professors feel about sex education being taught in secondary schools in the Raipurand Ranchi areas is the major goal of this research. The study's goals are to (1) identify the attitude andperception of sex education among secondary school Teacher's Trainees and faculties of B.Ed. colleges(2) determine the difference in the attitude of secondary school teacher trainees and B.Ed. faculty inareas aimed at sex education between colleges in Raipur and Ranchi and (3) assess the difference in theattitude of secondary school Teacher's Trainees and faculties of B.Ed. colleges between government andprivate schools. The purpose of this research is to examine the perspectives of secondary school maleand female Teacher's Trainees and faculty members from B.Ed. institutions on the topic of sex educationin the classroom, as well as to draw comparisons between these groups.